Anxiety Scores Related To Facing Death Before And After SEFT Therapy Based on Dzikir and Prayer - septo_nugroho15 septo; Diyah Yulistika Handayani; Dedy Purwito; Wahyu Riyaningrum (HealthCare Nursing Journal, 2025)
Old age represents the final stage in the human life cycle, during which individuals experience various changes as they enter the aging phase. Degenerative processes bring about numerous transformations, including psychosocial changes such as anxiety. One prominent source of anxiety among the elderly is the fear of death. Addressing this anxiety requires integrating spiritual elements, such as SEFT (Spiritual Emotional Freedom Technique) therapy based ondhikrand prayer.This study aimed to determine the difference in anxiety scores related to facing death before and after SEFT therapy based ondhikrand prayer among the elderly in Cijati Village, Cimanggu District, Cilacap Regency. This quantitative study employed a pre-experimental design with a pre-test and post-test approach. The sample consisted of 32 individuals aged 6070 years, selected using judgment sampling. Data were analyzed using the paired sample t-test. The findings revealed a significant difference in anxiety scores related to facing death before and after the SEFT therapy intervention based ondhikrand prayer, with a p-value of 0.000. It is concluded that there was a significant difference in anxiety scores related to facing death before and after SEFT therapy based ondhikrand prayer among the elderly in Cijati Village, Cimanggu Sub-District, Cilacap Regency.